First things first: a strategic communication campaign promoting the importance of fertility wellness among young Singaporean adults - Jacobus, Ezra Jeremiah (Nanyang Technological University, 2023)
First Things First is a strategic communication campaign that aims to increase awareness on fertility health and wellness amongst young couples and individuals between the ages of 21–35. Despite 1 in 6 Singaporeans suffering from infertility, 46% of Singaporeans have never worried about their fertility health. This is especially concerning as Singaporeans are by and large getting married at an older age when fertility typically declines. Through implementing a digital-first strategy, First Things First increased susceptibility among our target audience and raised their self-efficacy by emphasising on the timeliness of fertility wellness and the ease of uptake. Our messaging was centralised on the target audience’s own fertility health and the benefits of early detection of health issues that could affect their fertility, rather than on childbearing, to include those who do not want or are on the fence about having children. Over the course of our three-month campaign, First Things First succeeded in increasing awareness amongst couples and individuals who were exposed to our campaign by 30.8%. Moving forward, we hope for more societal and governmental support for those who are in the midst of their fertility wellness journey.